Persistent and recurrent ischemic mitral regurgitation - Troubil, Martin; Lonský, Vladimír; Gwozdziewicz, Marek; Bruk, Vilém (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2010)
BACKROUND: Ischemic mitral regurgitation (IMR) is a consequence of coronary artery disease and the main underlying mechanism is augmented leaflet tethering due to outward displacement of the papillary muscles. Although mitral annuloplasty combined with coronary revascularization is usually effective in the treatment of IMR, occasionally the regurgitation can persist or recur and this can affect patient prognosis. METHODS: We searched Medline and Google scholar database for articles published since 1996 to June 2009. Search terms included ischemic mitral regurgitation, recurrent mitral regurgitation, persistent mitral regurgitation and annuloplasty failure. CONCLUSION: This article reviews current knowledge about IMR, the reasons and mechanisms of persistent and recurrent mitral regurgitation. We review clinic and echocardiographic predictive factors associated with persistence a recurrence of mitral regurgitation after annuloplasty.
Keywords: echokardiografie; lidé; Mitral Valve Insufficiency; Prognosis; mitrální insuficience; Mitral Valve; Myocardial Ischemia; prognóza; koronární bypass; Coronary Artery Bypass; Humans; recidiva; Recurrence; Echocardiography; ischemická choroba srdeční; mitrální chlopeň